The Effect of Compensation and Work Discipline on Performance with Career Development as an Intervening Variable in PT Hutama Karya Infrastruktur Binjai-Brandan Zone IV - Muhammad Yuanto; M. Isa Indrawan; Mesra B. (International Journal of Management, Economic and Accounting, 2023)
This study aims to determine the effect of Compensation and Work Discipline on Performance with Career Development as an Intervening Variable at PT Hutama Karya Infrastruktur Binjai-Brandan Zone IV. The population and sample in this study were contract employees of PT Hutama Karya Infrastruktur Pembangunan Tol Pekanbaru-Padang, Padang Siring Section totaling 82 respondents. With sampling techniques, namely saturated samples. The data analysis technique in this study uses (SEM) structural equation modeling using the help of smartPLS. The results of this study showed that work discipline had no effect on performance. Work discipline affects career development. Compensation affects performance. Compensation affects career development. Career development affects performance. Compensation affects performance through career development as an intervening variable. Work discipline has no effect on performance through career development as an intervening variable.